2023
DOI: 10.1002/bmm2.12039
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials for in situ cell therapy

Abstract: Cell therapy has revolutionized the treatment of various diseases, such as cancers, genetic disorders, and autoimmune diseases. Currently, most cell therapy products rely on ex vivo cell engineering, which requires sophisticated manufacturing processes and poses safety concerns. The implementation of in situ cell therapy holds the potential to overcome the current limitations of cell therapy and provides a broad range of applications and clinical feasibility in the future. A variety of biomaterials have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 145 publications
(266 reference statements)
0
6
0
Order By: Relevance
“…These results altogether indicated that composite piezoelectric membrane possessed superior biocompatibility without obvious cytotoxic effect. The KNN nanowires have been identified to exhibit excellent biocompatibility both in vitro and in vivo in our previous work. , Besides, PCL-based implantable materials have been safely applied in tissue engineering. , US excitation at 1 MHz and 100 kPa was conducted using a customized device (Figure S5A). By controlling the US excitation time, programmable US-based electric cues were produced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results altogether indicated that composite piezoelectric membrane possessed superior biocompatibility without obvious cytotoxic effect. The KNN nanowires have been identified to exhibit excellent biocompatibility both in vitro and in vivo in our previous work. , Besides, PCL-based implantable materials have been safely applied in tissue engineering. , US excitation at 1 MHz and 100 kPa was conducted using a customized device (Figure S5A). By controlling the US excitation time, programmable US-based electric cues were produced.…”
Section: Resultsmentioning
confidence: 99%
“…5,22 Besides, PCL-based implantable materials have been safely applied in tissue engineering. 23,24 US excitation at 1 MHz and 100 kPa was conducted using a customized device (Figure S5A). By controlling the US excitation time, programmable US-based electric cues were produced.…”
Section: Resultsmentioning
confidence: 99%
“…Since there have been many comprehensive reviews concerning nanodelivery systems for in situ antigen‐presenting cell reprogramming, [ 24,29,38,39 ] for example, mRNA vaccines, we will not describe the advances of this field in this review. Instead, we will provide an overview of recent progress in the development of synthetic nanomaterials to deliver plasmid DNA or mRNA for in situ reprogramming of T cells and macrophages (summarized in Table 1 ), as they are the most attractive therapeutic cell populations of diverse immune‐related disorders (cancer, auto‐immune disease, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer immunotherapy has revolutionized current cancer treatment since its discovery due to its capacity to specifically eradicate tumor cells. [ 1–4 ] To date, we have witnessed the tremendous successes of immune checkpoint blockade (ICB) therapies and CAR‐T cell therapy in the clinic. However, only a small portion of patients, particularly those bearing solid tumors, can benefit from those clinically applied immunotherapies.…”
Section: Introductionmentioning
confidence: 99%